2021
DOI: 10.3934/dcdsb.2020186
|View full text |Cite
|
Sign up to set email alerts
|

On the unboundedness of the ratio of species and resources for the diffusive logistic equation

Abstract: proposed an optimization problem to consider the supremum of the ratio of the L 1 norms of species and resources by varying the diffusion rates and the profiles of resources, and moreover, he gave a conjecture that the supremum is 3 in the one-dimensional case. In [1], Bai, He and Li proved the validity of this conjecture. The present paper shows that the supremum is infinity in a case when the habitat is a multi-dimensional ball. Our proof is based on the sub-super solution method. A key idea of the proof is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…for some time horizon T > 0. This problem is the parabolic counterpart of a related elliptic optimisation problem that was intensively studied in the past few years, see section 1.6 and [20,23,24,28,30,31,35,39,40,43,44]. In the elliptic case, the bang-bang property for optimisers was, in particular, a question that drew a lot of attention [35,40,44] and was only recently settled in [39].…”
Section: Main Results For the Parabolic Problemmentioning
confidence: 99%
“…for some time horizon T > 0. This problem is the parabolic counterpart of a related elliptic optimisation problem that was intensively studied in the past few years, see section 1.6 and [20,23,24,28,30,31,35,39,40,43,44]. In the elliptic case, the bang-bang property for optimisers was, in particular, a question that drew a lot of attention [35,40,44] and was only recently settled in [39].…”
Section: Main Results For the Parabolic Problemmentioning
confidence: 99%
“…This conjecture is confirmed in [3]. However, for higher dimensional case, i.e., n ≥ 2, it is proved in [16] that the supremum of E(m) is unbounded. Some further studies related to this question can be found in [24,25].…”
Section: Introductionmentioning
confidence: 81%
“…The proof is an application of our result [20] on the profile of the positive stationary solution to a diffusive logistic equation. In [20], the authors proved that some spatial concentration setting of a resource function in the diffusive logistic equation makes the L 1 norm of the positive stationary solution become as large as possible. It will be shown that, in the case of d S = d I , (3) can be reduced to a single equation, which is similar to the stationary diffusive logistic equation.…”
Section: Introductionmentioning
confidence: 86%
“…By the setting of m(x) := β − γ(x) and v(x) := β w I(x), the function v(x) satisfies the diffusive logistic Equation ( 9). Subsequently, we can apply the results in [20] to v(x) (I(x)). Here, we define a positive constant…”
Section: Subsequently (3) Is Equivalent Tomentioning
confidence: 99%